Peningkatan Pengetahuan Ibu Usia Reproduktif Tentang Pemberian ASI Eksklusif Di Desa Aengdake Kecamatan Bluto - Damayanti, Cory Nelia; Kurniyati, Eka Meiri; Wardita, Yulia (PRAXIS: Jurnal Pengabdian kepada Masyarakat, 2024)
Exclusive breastfeeding is breast milk given to babies from birth for 6 (six) months, without adding and/or replacing it with other foods or drinks. Breast milk contains many nutrients, including albumin, fat, carbohydrates, vitamins, minerals, growth factors, hormones, enzymes, immune substances, and white blood cells in the right and balanced portions. The composition of breast milk is specific to each mother, changes and differs from time to time according to the baby's needs at that time. One of the obstacles to exclusive breastfeeding is the mother's low level of knowledge. The method used to increase this knowledge is by providing counseling in the form of interactive lectures and showing videos, while implementing behavior is carried out through exercises or simulations. Before the counseling was carried out, a pretest was carried out on mothers of reproductive age who were participants in community service. After being given counseling, a post test was carried out to see the increase in mother's knowledge. From the pretest results it was found that 40% did not have a good understanding of exclusive breastfeeding. After being given counseling, there was a significant increase in participants' understanding, namely 80%. The conclusion of this community service is that after receiving counseling, there was an increase in understanding regarding exclusive breastfeeding among mothers of reproductive age in Aengdake village.